2019
DOI: 10.1111/ppe.12543
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal risk factors with the recent rise of neural tube defects in Canada

Abstract: Background We sought to assess the recent trend in NTD prevalence at birth in the post‐folic acid food fortification era and to identify the maternal risk factors associated with that trend. Methods We carried out a population‐based study of all livebirths and stillbirths (including late pregnancy terminations) delivered in hospitals in Canada (excluding Quebec) from 2004 to 2015 (n = 3 439 330). We examined NTD birth prevalence by year, multiple pregnancy, maternal age, parity, pregestational diabetes, chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…The association of in utero exposure to teratogens with absolute microcephaly was, however, consistent with previous studies 13 18 19 26 37 38. Exposures to teratogens or substances such as cocaine, opioids and alcohol are known risk factors for microcephaly4 26 37 38 and other neurological developmental abnormalities 27. Another recent study from Quebec, Canada, found that neonatal abstinence syndrome (a proxy for exposure to maternal opioids exposure) was associated with a 16-fold higher risk (adjusted risk ratio 16.4, 95% CI 9.4 to 28.6) of congenital microcephaly 26…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association of in utero exposure to teratogens with absolute microcephaly was, however, consistent with previous studies 13 18 19 26 37 38. Exposures to teratogens or substances such as cocaine, opioids and alcohol are known risk factors for microcephaly4 26 37 38 and other neurological developmental abnormalities 27. Another recent study from Quebec, Canada, found that neonatal abstinence syndrome (a proxy for exposure to maternal opioids exposure) was associated with a 16-fold higher risk (adjusted risk ratio 16.4, 95% CI 9.4 to 28.6) of congenital microcephaly 26…”
Section: Discussionsupporting
confidence: 90%
“…We characterised maternal demographics and risk factors for the three types of microcephaly. We considered maternal age at conception (<25, 25–29, 30–34 and ≥35 years), mother’s ethnicity (Cantonese women vs women migrated from other provinces of China), parity (first vs ≥second child), conception method (IVF vs natural), pregnancy condition (ie, pre-existing hypertension, gestational hypertension, pre-eclampsia/eclampsia, gestational and pregestational diabetes mellitus),17 18 exposure to teratogens (ie, maternal use of substances or behavioural risk factors) including prenatal and/or perinatal use of alcohol, cigarette or medicinal or other illicit or therapeutic drugs13 26 27 and TORCH infections during pregnancy. In addition, we included congenital heart defects and other anomalies as the former has been strongly associated with microcephaly 3 5 13.…”
Section: Methodsmentioning
confidence: 99%
“…A recently study commented on the increase in NTD‐affected pregnancies in Canada over the past decade and how these additional cases may be due to increased prevalence of several risk factors including pregestational diabetes and certain conditions which are sometimes treated with AEDs such as epilepsy and mood disorders (Liu et al, ). In addition, despite the high prevalence of obesity and its established association with NTD risk, research is lacking on an appropriate FA dose that might help to reduce, though perhaps not eliminate, NTD risk for this group.…”
Section: Discussionmentioning
confidence: 99%
“…FA supplementation reduces the NTDs and other embryopathies described in the offspring of diabetic rodent dams . However, despite the efforts to prevent NTDs through FA supplementation in humans, no such decrease has been detected, and there is even a suggestion that their incidence may increase in association with pregestational diabetes . Significantly, this latter study was performed on a Canadian population where around 38% of the newborns carried the 677C>T allele for MTHFR , associated with reduced enzymatic activity …”
Section: Introductionmentioning
confidence: 92%
“…[32][33][34] However, despite the efforts to prevent NTDs through FA supplementation in humans, no such decrease has been detected, 35,36 and there is even a suggestion that their incidence may increase in association with pregestational diabetes. 37 Significantly, this latter study was performed on a Canadian population where around 38% of the newborns carried the 677C>T allele for MTHFR, 38 associated with reduced enzymatic activity. 25,31,39 Based on this situation, we set out to explore the possible additive teratogenic effect of these two risk factors on the developing embryo: a diabetic intrauterine environment and the presence of compromised maternal-fetal folate metabolism.…”
Section: Introductionmentioning
confidence: 99%